Advanced mechatronics and MEMS devices. II - Zhang, Dan, 1964-; Wei, Bin, 1987- (Springer, 2017)
"This book introduces the state-of-the-art technologies in mechatronics, robotics, and MEMS devices in order to improve their methodologies. It provides a follow-up to 'Advanced Mechatronics and MEMS Devices' (2013) with an exploration of the most up-to-date technologies and their applications, shown through examples that give readers insights and lessons learned from actual projects. Researchers on mechatronics, robotics, and MEMS as well as graduate students in mechanical engineering will find chapters on: Fundamental design and working principles on MEMS accelerometers Innovative mobile technologies ; Force/tactile sensors development ; Control schemes for reconfigurable robotic systems Inertial microfluidics ; Piezoelectric force sensors and dynamic calibration techniques ... and more. Authors explore applications in the areas of agriculture, biomedicine, advanced manufacturing, and space. Micro-assembly for current and future industries is also considered, as well as the design and development of micro and intelligent manufacturing"- Resumé vydavatel
Keywords: biomedicínské inženýrství; mechatronika; robotika; automatické řízení; nanotechnologie; strojní inženýrství; biomedical engineering; mechatronics; robotics; automatic control; nanotechnology; mechanical engineering; elektronické knihy; sborníky; electronic books; papers of several authors